IMPLEMENTATION OF MICROSOFT MATHEMATICS IN ENGINEERING MATHEMATICS - Kanakadurga Devi, P.; Naidu, V.G. (International Journal of Psychosocial Rehabilitation, 2021)
Microsoft Mathematics is a freely downloadable educational program. In this paperimplemented Microsoft Mathematics to develop the problem solving skills in EngineeringMathematics. In this survey two groups of students were participated. Conventional group waslearning by using age-old teaching method and Empirical group was learning by usingMicrosoft Mathematics. Assessment of student’s achievement was collected by conducting testbefore and after using Microsoft Mathematics. Using Microsoft Mathematics we can solveproblems related to Calculus, Statistics, Trigonometry and Linear Algebra. In this investigationEmpirical group students’ attitudes and self confidence in solving mathematical and tech relatedproblems comparing with Conventional group is more effective